2017
DOI: 10.1111/dom.13007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of liraglutide 3 mg vs structured lifestyle modification on body weight, liver fat and liver function in obese patients with non‐alcoholic fatty liver disease: A pilot randomized trial

Abstract: We compared the effects of weight loss induced by the glucagon-like peptide 1-agonist liraglutide with a structured lifestyle intervention in obese adults with non-alcoholic fatty liver disease (NAFLD). Obese (body mass index ≥30 kg/m , mean weight 96.0 ± 16.3 kg) non-diabetic Asian adults, with NAFLD diagnosed by liver fat fraction (LFF) ≥ 5.5% on magnetic resonance imaging without other causes of hepatic steatosis, were randomized to a supervised program of dieting (restriction by 400 kilocalories/d) plus mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 18 publications
4
73
0
9
Order By: Relevance
“…Our present study revealed that once-daily injection of liraglutide for 2 weeks decreased caloric intake and body weight, improved glucose tolerance, and protected from HFCC-CDX-induced insulin resistance, which are well-known effects of liraglutide in humans [27,28]. In addition, we observed that liraglutide could resolve hypertriglyceridemia and reduce hepatic steatosis, oxidative stress, and systemic and hepatic inflammation but not fibrosis, results that are in general agreement with the effects of liraglutide documented in preclinical studies with mice [29][30][31] and clinical trials for NASH [32][33][34]. In NAFLD patients, plasma ALT and AST levels have been found to decrease gradually during liraglutide treatment [32][33][34].…”
Section: -Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our present study revealed that once-daily injection of liraglutide for 2 weeks decreased caloric intake and body weight, improved glucose tolerance, and protected from HFCC-CDX-induced insulin resistance, which are well-known effects of liraglutide in humans [27,28]. In addition, we observed that liraglutide could resolve hypertriglyceridemia and reduce hepatic steatosis, oxidative stress, and systemic and hepatic inflammation but not fibrosis, results that are in general agreement with the effects of liraglutide documented in preclinical studies with mice [29][30][31] and clinical trials for NASH [32][33][34]. In NAFLD patients, plasma ALT and AST levels have been found to decrease gradually during liraglutide treatment [32][33][34].…”
Section: -Discussionsupporting
confidence: 89%
“…In addition, we observed that liraglutide could resolve hypertriglyceridemia and reduce hepatic steatosis, oxidative stress, and systemic and hepatic inflammation but not fibrosis, results that are in general agreement with the effects of liraglutide documented in preclinical studies with mice [29][30][31] and clinical trials for NASH [32][33][34]. In NAFLD patients, plasma ALT and AST levels have been found to decrease gradually during liraglutide treatment [32][33][34]. In our experimental setting, liraglutide could indeed significantly decrease the total NAFLD activity score but could not counter the HFCC-CDX-induced increase in plasma ALT and AST, in agreement with results from another dietary mouse model of NASH [30].…”
Section: -Discussionsupporting
confidence: 88%
“…In the Lira‐NAFLD study in obese diabetic adults, liver fat content decreased in association with liraglutide‐induced weight loss. Our pilot comparison study of liraglutide to lifestyle modification found that 26 weeks of daily liraglutide induced similar weight loss of ~4% and reductions in hepatic steatosis compared to a supervised structured programme of diet and exercise.…”
Section: Introductionmentioning
confidence: 92%
“…Multiple publications have reported beneficial effects to reduce liver fat content and improve ALT, and one study has suggested a benefit in reducing progression of fibrosis (5,10,34,50). Twenty publications reported the effects of a GLP-1 analog on liverrelated endpoints; 12 of these investigated liraglutide (5,6,11,19,20,22,34,44,50,60,65,66), and 8 investigated exenatide (10,13,14,17,18,55,56,58). Four of these reported randomized, controlled, double-blind studies of liraglutide with a placebo (n = 3) or active (n = 1) comparator, and only one of these, the "Liraglutide Safety and Efficacy in Patients with Non-alcoholic Steatohepatitis (LEAN)" study, assessed histological endpoints using biopsy.…”
Section: Glp-1 Agonistsmentioning
confidence: 99%